南極海の沿岸ポリニヤと定着氷のマッピング - 二橋, 創平; 大島, 慶一郎; Sohey, Nihashi; Kay, I. Ohshima (2013)
The active freezing in Antarctic coastal polynyas leads to dense water formation through large amount of brine rejection. The dense water is a major source of Antarctic Bottom Water (AABW) which is the densest water in the global overturning and is a key player in the climate change as a significant sink for heat and carbon dioxide. The Antarctic coastal polynyas are also the areas of high primary productivity. In some coastal polynyas, it was suggested that landfast sea ice (fast ice), which is a prominent feature of the Antarctic coastal zone, plays an important role in the polynya and AABW formation because it causes divergent ice motion by blocking ice advection. This study presents the first combined mapping of the coastal polynyas (ice production) and fast ice along the entire Antarctic coast using AMSR-E data. The spatial resolution of AMSR-E (about 6.25 km) is two times finer than that of SSM/I which was used in the previous study. This advantage of AMSR-E is critical for the detection of the coastal polynyas and fast ice because their spatial scales are typically less than tens of km. The mapping reveals strong linkage between the coastal polynyas and fast ice: most of the polynyas are formed on the western side of fast ice. The results from the analyses based on the mapping and meteorological dataset are summarized as follows: A wind diverging from the boundary defined by fast ice and land is the primary cause for the polynya formation. A blocking effect of fast ice on sea ice advected by the coastal current is another key factor. A drastic change in fast ice extent causes a dramatic change in the polynya area and ice production, suggesting that the fast ice change can be an important factor of the climate change. The findings of this study suggest that fast ice should be treated in future models for better climate projections. The mapping of this study gives the boundary/validation data of fast ice and ice production for such models. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 統計数理研究所 ３階セミナー室１（D305） ...